2020
DOI: 10.1111/hex.13027
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of care for people who had a stroke in a low‐/middle‐income country: A qualitative analysis of health‐care professionals’ perspectives

Abstract: Background and Objective Efforts to improve the adoption of evidence‐based interventions for optimal patient outcomes in low‐/middle‐income countries (LMICs) are persistently hampered by a plethora of barriers. Yet, little is known about strategies to address such barriers to improve quality stroke care. This study seeks to explore health professionals’ views on strategies to improve quality stroke care for people who had a stroke in a LMIC. Methods A qualitative interview study design was adopted. A semi‐stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Another study in South Africa [ 24 ] showed that stroke patients received only limited rehabilitation therapies through CBR, which did not exceed five sessions over a period of six months. The rehabilitation of patients with various forms of disabilities has not been prioritised in SSA because governments focus primarily on the burden of communicable diseases [ 10 , 25 ], but the increasing rate of non-communicable diseases calls upon the countries of SSA to respond to the growing trends of these diseases [ 1 , 10 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in South Africa [ 24 ] showed that stroke patients received only limited rehabilitation therapies through CBR, which did not exceed five sessions over a period of six months. The rehabilitation of patients with various forms of disabilities has not been prioritised in SSA because governments focus primarily on the burden of communicable diseases [ 10 , 25 ], but the increasing rate of non-communicable diseases calls upon the countries of SSA to respond to the growing trends of these diseases [ 1 , 10 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Training HCPs on stroke management is one of the strategies to improve the quality of care for stroke patients ( Rababah, Al-Hammouri & AlNsour, 2021 ; Baatiema et al, 2020 ). As a part of a nationwide initiative to improve stroke care in Malaysia, an online stroke e-learning module was launched to raise awareness of AIS management among HCPs ( Docquity.com, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for LMICs all over the world, who are haunted by political and economic injustices (Browne et al, 2016 ; Lavoie et al, 2018 ; Umeh & Feeley, 2017 ; Ziltener & Künzler, 2013 ). These injustices have resulted in several consequences such as severe inequity, high unemployment rates and insufficient health systems (Baatiema et al, 2020 ; Browne et al, 2016 ; Ruelas, Gómez-Dantés, Leatherman, Fortune, & Gay-Molina, 2012 ). This in turn has caused unsurmountable personnel and resource constraints, high patient numbers, as well as a complex burden of disease (Ludwick, Morgan, Kane, Kelaher, & McPake, 2020 ; Mayosi et al, 2012 ; Meng et al, 2020 ; Puchalski Ritchie et al, 2016 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This in turn has caused unsurmountable personnel and resource constraints, high patient numbers, as well as a complex burden of disease (Ludwick, Morgan, Kane, Kelaher, & McPake, 2020 ; Mayosi et al, 2012 ; Meng et al, 2020 ; Puchalski Ritchie et al, 2016 ). These constraints have forced HCPs to practice in a creative and flexible manner to combat the effect of these inequities on their patients (Baatiema et al, 2020 ; Saito et al, 2016 ; Van Graan, Williams, & Koen, 2016 ). For perceived non-essential services such as speech therapy, these difficulties are often compounded because of their lack of priority when disseminating resources (Andrews & Pillay, 2017 ; Bright, Wallace, & Kuper, 2018 ; Rech, Hugo, Schmidt, Goulart, & Hilgert, 2019 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%